2021
DOI: 10.1063/5.0068939
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of two-dimensional gallium-nitrides on van der Waals epitaxial substrate

Abstract: The structural and electronic properties of two-dimensional gallium nitrides (2D GaNs) on a van der Waals (vdW) epitaxial substrate are investigated using first-principles calculations. We show that the structures and electronic properties of mono- and bilayer GaN are hardly affected when deposited on the vdW substrate comprising a graphene sheet placed on the GaN(0001) bulk surface. A weak attractive interaction is found to work between the 2D GaNs and vdW substrate, which is still sufficient to maintain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Yayama et al grew 2D GaN on a thin graphene sheet, supported by bulk GaN. 155 The suggested growth method leads to 2D GaN possessing novel advanced electronic properties. The introduction of a thin graphene sheet could also reduce the high lattice mismatch between GaN and other substrates, such as the widely used Al 2 O 3 or Si.…”
Section: Semiconductor Photocathodesmentioning
confidence: 99%
“…Yayama et al grew 2D GaN on a thin graphene sheet, supported by bulk GaN. 155 The suggested growth method leads to 2D GaN possessing novel advanced electronic properties. The introduction of a thin graphene sheet could also reduce the high lattice mismatch between GaN and other substrates, such as the widely used Al 2 O 3 or Si.…”
Section: Semiconductor Photocathodesmentioning
confidence: 99%
“…In addition to the hexagonal structure, other 2D planar porous structures of GaN containing octagonal and square membered rings have also been simulated to expand its research scope [260,261]. Firstprinciples and molecular dynamics simulations have been performed on pristine and defective 2D GaN to study its mechanical response under varying strains, external loads as well as different temperatures [262][263][264][265][266][267][268]. It was found that the presence of vacancy defects leads to a decrease in the fracture limit compared with the perfect GaN nanosheets [269][270][271].…”
Section: D Ganmentioning
confidence: 99%